2008
DOI: 10.3181/0805-rm-140
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Antioxidants Enhance the Effects of Mesalamine in the Treatment of Chemically Induced Colitis in Rats

Abstract: Global assessments of microscopic colitis induced by TNBS indicated that 5-ASA alone significantly changed colonic injury by -31%. Combination therapy with ascorbic acid plus 5-ASA or alpha-tocopherol plus 5-ASA caused further significant change in TNBS colitis by -65 and -82%, respectively. Each of these values was significantly below scores observed with 5-ASA as monotherapy. Reduction in colitis with PBN plus 5-ASA was not different from 5-ASA alone. MPO activity was decreased significantly in response to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Studies also demonstrate that combination of 5-ASA with other antioxidants such as n-acetylcysteine produces better clinical and histological responses when compared with 5-ASA alone, suggesting that the capacity of reducing ROS in tissues is proportional to the increased antioxidant activity [53][54][55][56]. By such actions, 5-ASA can decrease or completely inhibit the oxidative DNA damage known to be involved in pathogenesis of UC, DC, and colitis-associated CRC [25,43,[58][59][60][61]. Although 5-ASA has been used in patients with UC, few studies have evaluated its therapeutic effects in patients with DC [40,41].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies also demonstrate that combination of 5-ASA with other antioxidants such as n-acetylcysteine produces better clinical and histological responses when compared with 5-ASA alone, suggesting that the capacity of reducing ROS in tissues is proportional to the increased antioxidant activity [53][54][55][56]. By such actions, 5-ASA can decrease or completely inhibit the oxidative DNA damage known to be involved in pathogenesis of UC, DC, and colitis-associated CRC [25,43,[58][59][60][61]. Although 5-ASA has been used in patients with UC, few studies have evaluated its therapeutic effects in patients with DC [40,41].…”
Section: Discussionmentioning
confidence: 97%
“…The importance of using antioxidants in treatment of DC is underscored by clinical study results demonstrating that 5-aminosalicylic acid (5-ASA) was equally effective in treatment of both ulcerative colitis (UC) and DC [40][41][42][43][44][45]. However, the effectiveness of 5-ASA in protecting against oxidative tissue damage in experimental models of DC has never been studied.…”
Section: Introductionmentioning
confidence: 98%
“…The dose of ARF used was chosen on basis of preliminary experiments, as the lowest to obtain safety and efficacy in the referred colitis rat model, and that of 5-ASA was as reported in literature [5,27] and taking into consideration the dose translation from animal to humans [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed the MPO activity elevation in both AA-and trinitrobenzenesulfonic acid-induced experimental colitis in rodents. 16,30 The second part of the current study was devoted to examine the gastroprotective effect of Crataegus monogyna berry extract and atorvastatin on the AA-induced colitis. Moreover, any possible interaction between test compounds was also investigated.…”
Section: Discussionmentioning
confidence: 99%